Folic Acid-Conjugated Fe-Au-Based Nanoparticles for Dual Detection of Breast Cancer Cells by Magnetic Resonance Imaging and Computed Tomography - Jamshidi, Nasim; Tarighatnia, Ali; Ghaziyani, Mona Fazel; Sajadian, Fakhrossadat; Olad-Ghaffari, Maryam; Nader, Nader D. (Frontiers in biomedical technologies, 2024)
Purpose: We synthesized folic acid-conjugated Fe3O4/Au-pralidoxime chloride Nanoparticles (Fe2O3/Au@PAM NPs) for use as dual-modal contrast agents for Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) in the diagnosis of breast cancer. Materials and Methods: Fe2O3/Au@PAM NPs labeled or not to folic acid were synthesized and analyzed by dynamic light scattering, transmission electron microscopy, and vibrating sample magnetometry. The ability of these NPs to create image contrast was also investigated in silico and in vitro (in MCF-7 breast cancer cells and A549 lung cancer cells) with CT and MRI. Results: Dynamic light scattering and transmission electron microscopy revealed that the Fe2O3/Au@PAM NPs were nearly spherical. The average diameter of Fe2O3/Au NPs increased from 11.6 nm to 98 nm after folic acid conjugation. The saturation magnetization values of Fe2O3/Au@PAM NPs with and without folic acid conjugation were 25.56 and 32.6 emu/g, respectively. Conjugation of folic acid to NPs greatly improved their uptake by cancer cells. The additional coating of NPs with FA reduced the T2 relaxation time and signal intensity for MRI. Folic acid-labeled MCF-7 cells had a radiodensity measurement of 208 Hunsfield Units (HU) compared to 95 HU for A549 cells. For breast cancer cells, NPs labeled with folic acid significantly improved the X-ray absorption coefficient as a sign of active cellular uptake compared to NPs without labeling. Conclusion: Folic acid-labeled Fe2O3/Au@PAM NPs can serve as dual CT/MRI contrast agents and improve the sensitivities of both modalities for the detection of cancer cells.